Surface diffusivity of cleaved NaCl crystals as a function of humidity: Impedance spectroscopy measurements and implications for crack healing in rock salt - Koelemeijer, P; Peach, C; Spiers, C (Wiley, 2012)
Rock salt offers an attractive host rock for geological storage applications, because of its naturally low permeability and the ability of excavation-induced cracks to heal by fluid-assisted diffusive mass transfer. However, while diffusive transport rates in bulk NaCl solution are rapid and well characterized, such data are not directly applicable to storage conditions where crack walls are coated with thin adsorbed water films. To reliably predict healing times in geological storage applications, data on mass transport rates in adsorbed films are needed. We determined the surface diffusivity in such films for conditions with absolute humidities (AH) ranging from 1 to 18 g/m 3 (relative humidities (RH) of 4%-78%) by measuring the surface impedance of single NaCl crystals. We use the impedance results to calculate the effective surface diffusivity S = DδC using the Nernst-Einstein equation. The S values obtained lie in the range 1 × 10-27 m3 s-1 at very dry conditions to 1 × 10-19 m 3 s-1 for the deliquescence point at 296 K, which is in reasonable agreement with existing values for grain boundary diffusion under wet conditions. Estimates for the diffusivity D made assuming a film thickness δ of 50-90 nm and no major effects of thickness on the solubility C lie in the range of 1 × 10-14 to 8 × 10-12 m 2 s-1 for the highest humidities studied (14-18 g/m 3 AH, 60%-78% RH). For geological storage systems in rock salt, we predict S values between 1 × 10-22 - 8 × 10-18 m3 s-1. These imply crack healing rates 6 to 7 orders of magnitude lower than expected for brine-filled cracks.